2016
DOI: 10.1111/jvp.12372
|View full text |Cite
|
Sign up to set email alerts
|

A large potentiation effect of serum on the in vitro potency of tulathromycin against Mannheimia haemolytica and Pasteurella multocida

Abstract: The antimicrobial properties of tulathromycin were investigated for M. haemolytica and P. multocida. Three in vitro indices of antimicrobial activity, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and time-kill curves, were established for six isolates of each organism. Each index was measured in two growth media: Mueller-Hinton broth (MHB) and calf serum. It was shown that MICs and MBCs were markedly lower in serum than in MHB. MHB:serum ratios for MIC were 47:1 (M. haemolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
8
20
0
Order By: Relevance
“…Supporting this notion, previous studies showed markedly lower azithromycin MICs against Pseudomonas aeruginosa in eukaryotic media and biological fluids such as serum and bronchoalveolar lavage fluid, compared with the recommended CA-MHB [15]. Similar observations were also noted for the potency of tulathromycin in calf serum against M. haemolytica and P. multocida [11]. This suggested that measuring MICs in eukaryotic media could be easily implemented to phenotypically detect acquired resistance to macrolides [16].…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Supporting this notion, previous studies showed markedly lower azithromycin MICs against Pseudomonas aeruginosa in eukaryotic media and biological fluids such as serum and bronchoalveolar lavage fluid, compared with the recommended CA-MHB [15]. Similar observations were also noted for the potency of tulathromycin in calf serum against M. haemolytica and P. multocida [11]. This suggested that measuring MICs in eukaryotic media could be easily implemented to phenotypically detect acquired resistance to macrolides [16].…”
Section: Discussionsupporting
confidence: 57%
“…This resulted in the underestimate of gamithromycin clinical efficacy by measuring MICs in broth medium. In fact, the serum effects on antimicrobial activity of macrolides have been reported for most fastidious respiratory pathogens [11,13]. In our study, the MICs of gamithromycin against H. parasuis in porcine serum were significantly lower than that in HTM.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations